The effect of dental caries on the colonization of Candida species: an in vitro study - Che Hussin, Harina Akila; Arshad, Nadiah; Ismail, Ahmad Faisal; Abllah, Zurainie; Arzmi, Mohd Hafiz (2019)
Introduction: Candida species are opportunistic microorganisms that inhabit oral cavity. The species of Candida that are normally isolated from the oral cavity include Candida albicans, Candida krusei and Candida glabrata. The objective of this study is to determine the effect of caries towards colonization of Candida spp. with the hypothesis that dental caries enhance the colonization of Candida spp. Materials and methods: To assess the colonization of Candida spp. in the oral cavity of paediatric patient, samples were obtained from 30 subjects aged five to six years old from International Islamic University Malaysia (IIUM) Dental Clinic and Adik Arif Kindergarten in Kuantan, Pahang, Malaysia. The samples were collected from buccal mucosa, palate and tooth surfaces using sterile swab. In addition, 10 mL of patient’s saliva suspension was also collected. Following that, the samples were inoculated aseptically on CHROMagar and incubated for 24 h to 48 h at 37 ºC. Finally, the colour, morphology and colony forming unit were determined. Results: This study has shown that no C. albicans was isolated from caries-free oral cavity. Meanwhile, 76% of children with caries possessed Candida spp. in their oral cavity with 65% of Candida spp. isolated was from the tooth surface. Only 35% of the total isolates were obtained from soft tissues including palatal and buccal mucosa. In addition, 82% and 67% of the yeast isolated from the tooth surface and buccal mucosa, respectively were C. albicans. Conclusion: In conclusion, dental caries enhances the colonization of Candida spp. in children’s oral cavity.